How Big is Too Big? The Girth of Bestselling Insertive Sex Toys to Guide Maximal Neophallus Dimensions. Issue 11 (1st November 2017) - Isaacson, Dylan; Aghili, Roxana; Wongwittavas, Non; Garcia, Maurice
Abstract: Background: In our practice we have encountered 4 female-to-male transgender patients seeking neophallus revision surgery for girth precluding penetrative vaginal or anal intercourse. Despite this, there is little evidence available to guide transitioning patients in neophallus sizing. In this work we examined the dimensions of bestselling realistic dildos, presuming that the most popular dimensions would reflect population preferences for penetrative toys and phalluses. Aim: To determine a maximal upper limit for girth compatible with penetrative intercourse based on measurements of bestselling realistic dildos and published erect penile dimensions. Methods: We collected measurements for "realistic dildos" designated as bestsellers for the top 5 Alexa.com-rated online adult retailers in the United States and for Amazon.com . We compared these with measurements of dildos available at Good Vibrations in San Francisco and with studies of erect natal dimensions. We compared all data with measurements of 4 index patients whose neophallus girth prevented penetrative intercourse. Outcomes: Length and circumference of overall bestselling and largest bestselling realistic dildos as reported on top websites and measured by investigators. Results: The average insertive length of the compiled dildos (16.7 ± 1.6 cm) was 1 SD longer than natal functional erect penile length as reported in the literature (15.7 ± 2.6 cm); however, their average circumference (12.7 ± 0.8 cm) mirrored natal erect penile girth (12.3 ± 1.3). The average girth of vendors' top 3 largest-girth dildos was 15.1 ± 0.9 cm, 2 SD wider than natal erect penile girth. Index patients had an average length of 16.3 ± 3.2 cm and an average girth of 17.6 ± 1.3 cm. Index patient girth was 4 to 5 SD wider than the average natal erect girth. Clinical Implications: Based on our data, we suggest that a surgically created neophallus should have a girth no wider than 15.1 cm after implantation of an inflatable penile prosthesis. This corresponds to 2 SD wider than the average natal man's erect girth. Strengths and Limitations: Strengths include in-person measurements of patients whose girth prevented penetrative intercourse, the large number of dildos assessed, and correlations with in-person measurements. Limitations include the inability to account for the pliability of different materials, whether dildos were used for vaginal and/or anal insertion, the limited sample of 4 transmen for in-person measurement, and the absence of implanted inflatable penile prostheses in index neophalluses. Conclusions: Neophallus girth wider than 15.1 cm could lead to difficulty in penetrative intercourse for many individuals. A conservative recommendation for neophallus girth is 13 to 14 cm, or 0.5 to 1.5 SD wider than natal erect penile girth.